2020
DOI: 10.1159/000513179
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for the Testing of Tissue Donors for Human Immunodeficiency Virus, Hepatitis B Virus, and Hepatitis C Virus

Abstract: <b><i>Background:</i></b> Although transmission of pathogenic viruses through human tissue grafts is rare, it is still one of the most serious dreaded risks of transplantation. Therefore, in addition to the detailed medical and social history, a comprehensive serologic and molecular screening of the tissue donors for relevant viral markers for human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) is necessary. In the case of reactive results in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Despite the suitability of validated assays for the serological screening of cadaveric samples, in a study by Larscheid et al [ 16 ] the total IgG in post-mortem blood samples of tissue donors was significantly lower when compared to pre-mortem blood samples. This highlights the utility of additional NAT-based screening for the confirmation of negative, equivocal, or weakly positive test results, thus increasing the safety of tissue preparations [ 17 , 18 ]. Regarding the NAT-based assays validated in our study, all examined assays were able to detect all HBV, HCV, and HIV spiked and unspiked pre- and post-mortem samples with no significant deviations of virus concentrations and internal QCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the suitability of validated assays for the serological screening of cadaveric samples, in a study by Larscheid et al [ 16 ] the total IgG in post-mortem blood samples of tissue donors was significantly lower when compared to pre-mortem blood samples. This highlights the utility of additional NAT-based screening for the confirmation of negative, equivocal, or weakly positive test results, thus increasing the safety of tissue preparations [ 17 , 18 ]. Regarding the NAT-based assays validated in our study, all examined assays were able to detect all HBV, HCV, and HIV spiked and unspiked pre- and post-mortem samples with no significant deviations of virus concentrations and internal QCs.…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopically abnormal cadaveric serological samples should be interpreted with care [ 19 ]. In addition, haemodilution and other factors also need to be assessed when screening is performed [ 17 ]. Studies showed that the timeframe of post-mortem taken blood samples may be further extended >24 h with serological and NAT assays still generating valid test results [ 5 , 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these are viral infections that can be disseminated via sexual contact, blood or by the use of blood products, and even through methods of intra-familial transmission [20]. As claimed by the World Health Organization (WHO) approximately two billion individuals have been exposed to this virus, out of which 240 million are long lasting carries [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C and hepatitis B are major health-related issues all over the globe [1]. Both of these are viral infections that can be disseminated via sexual contact, by blood or the use of blood products, and through methods of intra-familial transmission [2]. According to the World Health Organization (WHO), approximately two billion individuals have been exposed to Hepatitis C virus, out of which 240 million are long lasting carriers [3].…”
Section: Introductionmentioning
confidence: 99%